2017
DOI: 10.1080/17435390.2017.1309704
|View full text |Cite
|
Sign up to set email alerts
|

Harmful at non-cytotoxic concentrations: SiO2-SPIONs affect surfactant metabolism and lamellar body biogenesis in A549 human alveolar epithelial cells

Abstract: The pulmonary delivery of nanoparticles (NPs) is a promising approach in nanomedicine. For the efficient and safe use of inhalable NPs, understanding of NP interference with lung surfactant metabolism is needed. Lung surfactant is predominantly a phospholipid substance, synthesized in alveolar type II cells (ATII), where it is packed in special organelles, lamellar bodies (LBs). In vitro and in vivo studies have reported NPs impact on surfactant homeostasis, but this phenomenon has not yet been sufficiently ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
(67 reference statements)
1
23
0
Order By: Relevance
“…Meanwhile, we could conclude the surface tension of alveoli through the hysteresis of the P-V loop [ 34 ], which is influenced by the pulmonary surfactant [ 35 ]. It is a complicated phospholipid and protein complex synthesized and secreted by AECII [ 10 ] and packed in LBs [ 36 ]. It could maintain the surface tension [ 37 ], prevent the hyperinflation and collapse of alveoli, and hold a stable alveoli space.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we could conclude the surface tension of alveoli through the hysteresis of the P-V loop [ 34 ], which is influenced by the pulmonary surfactant [ 35 ]. It is a complicated phospholipid and protein complex synthesized and secreted by AECII [ 10 ] and packed in LBs [ 36 ]. It could maintain the surface tension [ 37 ], prevent the hyperinflation and collapse of alveoli, and hold a stable alveoli space.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal overloading with indigestible substances like NPs may lead to severe degenerative alterations of the cells. This indicates that supposedly inert but biopersistent nanomaterials can be harmful by interfering with normal endo-lysosomal functioning [9]. Lysosomal destabilization has already been shown as a cytotoxicity mechanism of TiO 2 NPs in human bronchial epithelial cells and in murine fibroblast cells [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to versatile NP-cell interactions and a variety of cellular responses [1]. Numerous investigations have already been conducted that studied cell interactions with various types of NPs, from polymeric NPs [2], lipid-based NPs [3], carbon based NPs [4,5,6], and metal oxide NPs [7,8,9]. Nevertheless, numerous NPs with modified or new properties are being developed every day, and understanding their interactions with cells and cellular responses is an important scientific issue that has to be addressed in order to assure their safe and efficient use [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A number of studies have described the acute toxicity of the IONPs in animals. [6][7][8][9] while other studies reported no apparent signs of toxicity. 3,9,10 Understanding the toxicological proles of IONPs, a transition metal is vital to ensure that the products are safe and developed with maximum benets and minimal risks.…”
Section: Introductionmentioning
confidence: 92%